Overlooked Husbands: The Paradox of Unfree Marriage in the Carolingian World. Issue 2 (17th January 2021) - Stone, Rachel
Abstract: Unfree people in the Roman world could not legally marry, while they could in the Middle Ages. This paper explores the marriage of the unfree in the Carolingian empire (750–900 CE), a society with an intense moral concern about marriage. Carolingian churchmen wrote extensively about marriage, using a strongly gendered discourse focusing on how men should approach marriage and behave as husbands. However, these moral and legal texts rarely discussed unfree marriage, even though the practice was common. It is argued that this silence reflects the persistence of late antique class‐based gender models, in which masculinity was reserved for married property holders. Although legal prohibitions on unfree marriages had ended, Carolingian moralists continued to be influenced by patristic assumptions that these were not valid relationships. These assumptions, combined with Frankish social practices that largely excluded unfree men from other key male roles, such as arms‐bearing, meant that unfree husbands were not conceptualised as sufficiently 'manly' to have their marriages discussed. It is only from the tenth century onwards, when images of masculinity began to fragment more along lines of social status, that authors began explicitly to state that the Christian ideas of marriage applied to all, free and unfree.